2021
DOI: 10.1002/jso.26517
|View full text |Cite
|
Sign up to set email alerts
|

The learning curve for uniportal video‐assisted thoracoscopic anatomical segmentectomy

Abstract: Objectives: The aim of this study is to evaluate the time course and caseload required to achieve proficiency by plotting the learning curve of uniportal thoracoscopic segmentectomy.Methods: We retrospectively analyzed the first 238 and 159 cases of uniportal thoracoscopic segmentectomy performed by two surgeons (A and B). The learning curves were assessed using cumulative sum analysis. Perioperative outcomes were evaluated as the learning curve developed. Two subtypes of this surgical approach, simple and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
(71 reference statements)
0
8
1
Order By: Relevance
“…We believe that cumulative experience was not a significant confounding factor since the two groups were contemporary. Albeit the uniportal learning curve can have a negative effect on operating time and perioperative complications (22,23), we did not find a difference in perioperative outcomes. Furthermore, once the UVATS technique was adopted by the three uniportal surgeons, this approach was used exclusively thereafter which could explain the shorter operating time found in our series.…”
Section: Discussioncontrasting
confidence: 64%
“…We believe that cumulative experience was not a significant confounding factor since the two groups were contemporary. Albeit the uniportal learning curve can have a negative effect on operating time and perioperative complications (22,23), we did not find a difference in perioperative outcomes. Furthermore, once the UVATS technique was adopted by the three uniportal surgeons, this approach was used exclusively thereafter which could explain the shorter operating time found in our series.…”
Section: Discussioncontrasting
confidence: 64%
“…The question we addressed is how many complex segmentectomies are needed to reach proficiency. Several studies have explored the learning curve for VATS anatomical segmentectomy, encompassing multiport, two-port, and uniportal access techniques ( 12 - 15 ). Dimitrovska and her colleagues observed that the inflection point in the learning curve was reached after conducting 47 cases, with surgeons attaining proficiency after performing 57 cases ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dimitrovska and her colleagues observed that the inflection point in the learning curve was reached after conducting 47 cases, with surgeons attaining proficiency after performing 57 cases ( 13 ). Li and colleagues determined that mastering uniportal VATS anatomical segmentectomy required approximately 64 to 71 cases, while achieving proficiency necessitated around 90 to 100 cases ( 12 ). However, research on the learning curve for uniportal VATS complex segmentectomy is relatively limited.…”
Section: Discussionmentioning
confidence: 99%
“…So far, studies have been carried out in large-volume centers to analyze the learning curve of U-VATS lobectomy regardless of video review (Table 2) (7,(18)(19)(20). According to the results of these study, about 57-140 cases are needed to attain the proficient phase.…”
Section: Discussionmentioning
confidence: 99%